The dual effects of anesthetics on glial cells: a review of neuroprotection and neurotoxicity - Wang, Xiaodong; Zhao, Minghe; Liu, Zhihui (Frontiers in Pharmacology, 2026)
Glial cells—comprising astrocytes, microglia, and oligodendrocytes—are fundamental to central nervous system (CNS) homeostasis, yet their interactions with anesthetics are not fully elucidated. This review narratively synthesizes current evidence on the differential effects of local and general anesthetics on these cells, revealing a complex duality of neuroprotective and neurotoxic outcomes. Local anesthetics such as lidocaine can confer protection by inducing astrocytic autophagy and suppressing microglial pro-inflammatory responses, whereas bupivacaine may impair astrocytic mitochondrial function and potentiate excitotoxicity. Conversely, general anesthetics exhibit divergent impacts: propofol demonstrates protective properties against oxidative stress and neuroinflammation, but isoflurane often induces astrocytic cytotoxicity, activates microglia via the NF-κB pathway, and triggers apoptosis in developing oligodendrocytes, thereby disrupting myelination. These effects are critically influenced by anesthetic type, concentration, exposure duration, and the pathological context. Our analysis underscores the necessity of understanding these glial-centric mechanisms to optimize anesthetic safety, particularly for vulnerable populations such as the young and the elderly. Ultimately, advancing the knowledge of how anesthetics modulate glial cell function is pivotal for developing personalized anesthesia strategies that minimize neurotoxicity and harness potential protective effects, thereby improving postoperative neurological outcomes and guiding future translational research.